2018
DOI: 10.1111/php.12951
|View full text |Cite
|
Sign up to set email alerts
|

Non‐mammalian Hosts and Photobiomodulation: Do All Life‐forms Respond to Light?

Abstract: Photobiomodulation (PBM), also known as low-level laser (light) therapy, was discovered over 50 years ago, but only recently has it been making progress toward wide acceptance. PBM originally used red and near-infrared (NIR) lasers, but now other wavelengths and non-coherent light-emitting diodes (LEDs) are being explored. The almost complete lack of side effects makes the conduction of controlled clinical trials relatively easy. Laboratory research has mainly concentrated on mammalian cells (normal or cancer)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 109 publications
1
36
0
1
Order By: Relevance
“…In fact, the review by Hamblin et al . clearly shows how PBM affects the cell behavior from bacteria up to vertebrate animals thought protozoa, fungi, invertebrate deuterostomes ( i.e . Paracentrotus lividus ) and protostomes ( i.e .…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the review by Hamblin et al . clearly shows how PBM affects the cell behavior from bacteria up to vertebrate animals thought protozoa, fungi, invertebrate deuterostomes ( i.e . Paracentrotus lividus ) and protostomes ( i.e .…”
Section: Commentarymentioning
confidence: 99%
“…In addition, with regard to the repeatability of the PBM effects on all life‐forms (for instance, the increment of cell proliferation as reviewed by Hamblin et al . ), it is not a coincidence that the specific chromophore‐target of PBM, the complex IV, is the cytochrome c oxidase of the mitochondrial respiratory chain of eukaryotes, which is presented also as large transmembrane protein complex in bacteria . Therefore, the electron transfers can similarly take place on the inner part of the cell membrane of prokaryotic cells or in specialized protein complexes in the inner membrane of the mitochondria of eukaryotic cells, and the generated electrochemical gradient makes ATP by oxidative phosphorylation.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…In both the organelles, the same set of functional genes for electron transport chain proteins is encoded; they show common stereo‐selective biochemical pathways and their molecular biology/bioenergetics share basic chemical processes . Authors pointed out that cytochrome‐c‐oxidase or complex IV, which is present also as large transmembrane protein complex in bacteria , is the specific chromophore's target of PBM at the red (600‐700 nm) and NIR (760‐900 nm) wavelength regions . Conversely, Complexes I and II are not affected by those wavelengths, while at 808 nm, the complex III is poorly stimulated by higher energies .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the light–chromophore interaction is reflected in modulation of adenosine triphosphate (ATP) production . These evidences explain because, in the range of 600 to 810 nm, PBM affects the cell behavior from bacteria and protozoa up to animals and humans and have been the most employed wavelengths for PBM . In recent years, it was suggested that the infrared region of the spectrum could influence other chromospheres, despite the interaction by wavelengths higher than 900 nm, and particularly 1064 nm, with mitochondrial chromophores was not clearly demonstrated .…”
Section: Introductionmentioning
confidence: 99%